Psychosocial conditions of quality of life for women during menopause treated for breast cancer - Pacian, Anna; Kulik, Teresa Bernadetta; Chruściel, Paweł; Pacian, Jolanta; Skórzyńska, Hanna; Zakrzewska, Wioleta (Menopause Review/Przegląd Menopauzalny, 2012)
Objectives: Breast cancer is one of the most frequent malicious tumours in women around the world. The highest incidence of the disease is registered among women aged 50 and more. Cancer imposes a considerable psychological strain on a woman. It causes a sense of uncertainty about one’s health and further life, as well as frequent problems with accepting the image of one’s own body. It often results in low self-esteem and a feeling of embarrassment, accompanied by symptoms of apathy and being self-contained. Despite a significant mental strain and many difficult moments, the majority of women manage to return to emotional balance owing to their will to survive and social support. Design : The aim of the discussed research was to determine quality of mental and social life of women in the menopause period treated for breast cancer. Material and methods : The research covered 107 women aged between 45 and 65 (SD = 6.11) undergoing treatment for breast cancer. The scale WHOQOL-Bref was applied in the research. Results : Examined areas and overall quality of life were evaluated more positively by women with higher education, who are single and live in rural areas. The paper demonstrates a correlation between self-evaluation of general quality of life and assessment of the social sphere of life. Conclusions : Perception of the overall quality of life and examined areas was generally good. Respondents have evaluated the mental sphere more negatively in comparison to the social sphere of quality of life. Demographic factors (age, education, place of residence) have had an influence on the quality of life in the examined group of women.